The Innovation and Challenges of Information and Communication Technology (ICT) in the Management of Education - Salau, K. K.; Adebayo, M. S.; James, O. R. (International Journal of Educational Management, 2021)
Innovation has to do with investing new ideas, software or hardware materials and its usage at facilitating needed solutions to tasks. Information and communication technology in education management has proved to be a watershed development.This paper, therefore, highlights among others its contributions in the realm of academic research, and programme instructions such as – Tutorial mode, Drill and practice mode, discovery mode, simulation mode, gaming mode, management information system (MIS), etc., which has benefited the management of education, but has inherent challenges. Such challenges are highlighted coupled with recommendations on how best to tackle them which includes adequate funding for procurement, installation and maintenance of ICT facilities, exercise of government needed political and legal will among others. If this challenges are well addressed, ICT will further enthrone blended – learning and improve the quality of education management.